2017
DOI: 10.1177/0363546516678723
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Benefit in Anterior Cruciate Ligament Reconstruction in Patients Older Than 60 Years?

Abstract: ACL reconstruction in active patients older than 60 years without arthritis restored knee stability in all treated cases. In these patients, as in younger age groups, ACL reconstruction showed good results on functional recovery while not increasing the risk of midterm functional knee deterioration or evolution of knee arthritis. The majority of patients returned to activities at their preinjury level. These data show that older and active patients with nonarthritic ACL-deficient knees need not be excluded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 15 publications
5
93
0
Order By: Relevance
“…20 With the advent of an anatomic surgical technique, the availability of enhanced instrumentation, the use of an improved and more aggressive rehabilitation protocol, and a better understanding of the immediate and long-term consequences of untreated knee instability, surgical indications for ACL insufficiency have been extended to active patients of all ages. 29 …”
mentioning
confidence: 99%
“…20 With the advent of an anatomic surgical technique, the availability of enhanced instrumentation, the use of an improved and more aggressive rehabilitation protocol, and a better understanding of the immediate and long-term consequences of untreated knee instability, surgical indications for ACL insufficiency have been extended to active patients of all ages. 29 …”
mentioning
confidence: 99%
“…The authors concluded that age over 50 years is not a contraindication to select a hamstring autograft for ACLR. 55 Toanen et al 56 demonstrated that older and active patients >60 years without osteoarthritis showed good results after single-bundle hamstring autograft ACLR. The majority of patients (83%) returned to sports activities with 50% returning to their preinjury level of activity.…”
Section: Resultsmentioning
confidence: 99%
“…The first study of patients who had ACL reconstruction after 60 years of age was reported in January 2017 by Toanen et al [15]. Only 12 patients were included.…”
Section: Discussionmentioning
confidence: 99%